Prevention of Deep Vein Thrombosis following Total Hip Replacement by Low Molecular Weight Heparinoid - Hoek, J A; Nurmohamed, M T; Hamelynck, K J; Marti, R K; Knipscheer, H C; ten Cate, H; Büller, H R; Magnani, H N; ten Cate, J W (Thrombosis and Haemostasis, 1992)
We assessed the safety and efficacy of the novel low molecular weight heparinoid Lomoparan (Org 10172) for the prevention of deep-vein thrombosis in patients undergoing elective total hip replacement in a randomized, placebo-controlled, double-blind trial in 197 consecutive patients. The heparinoid (750 anti-factor Xa-units, s. c., b.i.d.) was administered to 97 patients and 99 patients received placebo. Study medication was started preoperatively and continued for 10 days. Efficacy was assessed by bilateral phlebography at day 10, postoperatively.The incidence of deep-vein thrombosis was 56.6% and 15.5% respectively in the placebo and heparinoid treated patients (incidence reduction: 74%; P <0.001). This reduction was observed both for proximal-vein thrombosis (25% to 8%; P <0.005) and isolated calf-vein thrombosis (31% to 7%; P <0001.No major hemorrhage was observed. The number of red-cell units transfused and drain-fluid loss were comparable for the two study groups. Six patients in the heparinoid group and none in the control group developed minor wound hematomas (P <0.05).During an 8-week post-discharge follow-up period three patients with a normal venogram at day 10 developed clinically apparent venous thromboembolism, which was confirmed by objective testing. All three patients belonged to the heparinoid-treated group.We conclude that 750 anti-factor Xa units Org 10172 s.c. twice daily starting preoperatively is safe and effectively reduces early deep-vein thrombosis following elective total hip replacement. Further studies on the incidence of post-discharge thromboembolism are required.